Jump to content
BrainDen.com - Brain Teasers
  • 0
BMAD

A formal proof for x^2 = 2^x

Question

4 answers to this question

Recommended Posts

  • 0

Starting from the raising power operator, defined between two numbers x and y over a number field, xis not the same as yx, due to the missing commutativity property respect than the other sum and multiplication rank binary operators.

So this post is questioning for wich value of x in natural, integers, reals (or complex) number fields this identity is verified:

x2  = 2x .

This is what we call an equation to solve.

This problem could also be interpreted geometrically asking in which points the parabola y=x2 intersect the esponential function y=2x.2072127321_x22x.jpg.c8abc62d326ecea8fe79d5412e4bc93b.jpg

Before we start exploring over the natural number (positive integers), we know that 2x > 0 and x≥ 0 for every x Reals.

So, we can exclude immediatly the case for the integer x=0 wich implies:  02 < 20,, that is 0 < 1.

Furthermore, for the same reason and due to negative power of 2, for every negative integer x ≤ 1, we have 2x < x2 .

So, for positive integers x>0, both 2xand xare crescent functions 2x+1 ≥ 2x and (x+1)≥ x2,
and by the fact that:
   for x=112 <21 (that is 1 < 2), and
   for x=3, 3>23 (that is 9>8),
this implies that an integer solution is between 1 and 3.

Hence, our 1st trivial solution is for x=2:   22 = 2= 4 .

In a similar way, from the fact that at x=5 , we have  25 = 32 > 52 = 25, we candidate next integer solution to be between 3 and 5, that is x=4.

Analizing the number 4 as result of this 1st trivial solution,  It is interesting to observe that the number 2 let the 4 = 2+2 = 2*2 = 2^2 = ... ,  for every rank of the binary operator used.

4^2 = (2^2)^2 = 2^(2*2) = 2^(2+2) = 2^4 = 16.  (Notice that just for the positive integer 2 you can make (2^2)^2 = 2^(2^2) )
From this point on, infact, 2^x will exceed x^2 for every real x>=4, so no more positive real solution after 4.

Infact for every integer x>0
(x+4)2 ≤ 2(x+4)   ,     applying log in base 2 to both members, we can compare
2 log2(x+4) ≤ x+4 ≤ x+4 + x+4 ≤ 2(x+4)
log2(x+4) ≤ x+4 , for every real x>0.
So for every x>4 we proved that  x2 ≤ 2x.

But it's not the only interval where 2x exceeds x2.
infact,
x2 = 2x , can be rewritten as 2nd grade equation giving the:
x = 2x , and x = 2-x solutions.

Using the fact that
(-x)2 = 2x , or
(x)2 = 2-x 
x = 2-x/2

From the theorem of the fixed point applied to our exponential,
starting from x0=1, 
and proceeding recursively
x1 = -2x0/2 = -√2
x2 = -2x1/2 = -√2-1/√2
x3 = -2x2/2 = -√2-√2/2
...
xn = -2xn-1  = -√2-√2^(-√2^....n-1Times....^-√2))

The greater will be n and the smaller will be the difference xn+1 -xn.
The limit for n that tends to infinity of xis equal to value x:

x1  = 1
x1  = -1.41421356237310...
x2  = -0.612547326536066...
x3  = -0.808727927081827...
x4  = -0.755569324854238...
x5  = -0.769618475247432...
x6  = -0.765880261444542...
x7  = -0.766873153047868...
x8  = -0.766609309719418...
x9  = -0.766679412545762...
x10 = -0.766660785691404...
x11 = -0.766665734944187...
x12 = -0.766664419898679...
x13 = -0.766664769313767...
x14 = -0.766664676472171...
x15 = -0.766664701140715...
x16 = -0.766664694586141...
x17 = -0.766664696327729...
x18 = -0.766664695864979...
x19 = -0.766664695987935...
x20 = -0.766664695955265...
x21 = -0.766664695963945...
x22 = -0.766664695961639...
x23 = -0.766664695962252...
x24 = -0.766664695962089...
x25 = -0.-66664695962132...
x26 = -0.766664695962121...
x27 = -0.766664695962124...
x28 = -0.766664695962123...

x29 = -0.766664695962123...

The value asimptotically converge quickly according the desired precision.

Another method to find a closed form using the Lambert function W(z) = z ez,
which gives the solution in function of 

 1293751714_x22xSolutions.jpg.8ecc955fa3a4ad15320ba0680c55a7b9.jpg

F. Prowedi

Share this post


Link to post
Share on other sites
  • 0

x=2 and 4.
Proof:

22 = 22

42 = (22)2 = 24.

The third solution is x = -.76666468...., found numerically, looking for closed form.

Share this post


Link to post
Share on other sites
  • 0

Using natural logarithms, the equation becomes

x = 2 ln(x)
  1. x = 2 = 2 ln (2) = 2 x 1 = 2
  2. x = 4 = 2 ln (4) = 2 x 2 = 4

The third root is negative and solves

x = -2 ln (x)

Which has no algebraic solution.
Numerically, it's

x = -0.766664695 ....

Interested to find out what you mean by formal proof.

Share this post


Link to post
Share on other sites

Join the conversation

You can post now and register later. If you have an account, sign in now to post with your account.

Guest
Answer this question...

×   Pasted as rich text.   Paste as plain text instead

  Only 75 emoji are allowed.

×   Your link has been automatically embedded.   Display as a link instead

×   Your previous content has been restored.   Clear editor

×   You cannot paste images directly. Upload or insert images from URL.

Loading...

  • Recently Browsing   0 members

    No registered users viewing this page.

×
×
  • Create New...